Analysis of Visitor Satisfaction Based on the 4A Aspects at the Tomb of Sheikh Armia bin Kurdi Tegal - Risqi, Aulia Rima Dini; Rofi'ah, Haning; Suryorini, Ariana; Listyowati, Listyowati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
Visitor satisfaction is an important aspect of the successful development of a tourist spot. Tourist attractions will act wisely by measuring visitor satisfaction regularly, because that is one of the keys to retaining visitors. Therefore, to find out the level of visitor satisfaction, it must be seen from the aspects of the components of tourist destinations that are at the Tomb of Sheikh Armia Bin Kurdi Kurdi Tegal. This study aims to determine and explain visitor satisfaction based on the components of tourist destinations (4A) consisting of indicators of attraction, accessibility, amenity and ancillary religious tourism at the Tomb of Sheikh Armia Bin Kurdi Tegal. This research is located at the Tomb of Sheikh Armia Bin Kurdi, Cikura Village, Bojong District, Tegal Regency with a sample of 70 visitors who have visited the Tomb of Sheikh Armia Bin Kurdi Tegal. This study uses quantitative research, the sampling technique used in this study is purposive sampling. This type of online questionnaire using Google Form is used for the data collection method. This study uses IPA (Importance Performance Analysis) analysis. The results showed that visitor satisfaction consisted of the very good/high tourist destination component (4A) from the Performance level (Reality) while the Expectation Performance (Urgency) was not good/moderate and visitor satisfaction was categorized as good/high indicating visitors to Religious Tourism at the Sheikh's Tomb Armia Bin Kurdi Tegal is feeling Satisfied.